2018
DOI: 10.1111/papt.12167
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study: experiences of stigma by people with mental health problems

Abstract: People referred to their mental health diagnosis as a label and associated that label with stigmatizing views. Promote awareness and develop improved strategies (e.g., training) to tackle the cyclical impact of the 'hierarchy of labels' on people with mental health problems, their friends and family, and institutional stigma. Ensure the implementation of clinical guidelines in providing peer support to help people to combat feeling stigmatized. Talking about mental health in psychological therapy or health car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 45 publications
2
45
0
1
Order By: Relevance
“…Claimants in these focus groups described having a stigmatised identity, which is externally imposed on them. Such institutional stigma against people who claim benefits for a mental health problem has been reported in other research (Huggett et al, 2018) and without a change in societal attitudes, claimants are highly unlikely to escape from negative experiences associated with a social stigma.…”
mentioning
confidence: 65%
“…Claimants in these focus groups described having a stigmatised identity, which is externally imposed on them. Such institutional stigma against people who claim benefits for a mental health problem has been reported in other research (Huggett et al, 2018) and without a change in societal attitudes, claimants are highly unlikely to escape from negative experiences associated with a social stigma.…”
mentioning
confidence: 65%
“…Persons with their own experiences, so called peers, were regarded as trustworthy because they shared similar experiences as the participants. In fact, peers can help to combat stigma and being part of a peer support network can offer space to focus on other aspects than mental illness [42]. Concerning involvement of next of kin, it has been suggested that families are invited to be involved in the treatment [43].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with mental health problems such as psychosis experience severe negative attitudes and discrimination from the public (Barry, McGinty, Pescosolido, & Goldman, 2014; Corrigan, Markowitz, Watson, Rowan, & Kubiak, 2003; Crisp, Gelder, Rix, Meltzer, & Rowlands, 2000; Huggett et al, 2018; Phelan, Link, Stueve, & Pescosolido, 2000; Wood, Birtel, Alsawy, Pyle, & Morrison, 2014). Beliefs about mental disorders (causal attributions) and about people with mental disorders (stigma) can be detrimental for people’s well-being (Carter, Read, Pyle, & Morrison, 2017; Rüsch, Angermeyer, & Corrigan, 2005).…”
mentioning
confidence: 99%